SEMIOTICS ON GOTILON BATAK TOBA CEREMONY IN DOLOK SANGGUL HUMBANG HASUNDUTAN - JERLIN HUTASOIT; MORADA TETTY; SISILA FITRIANY DAMANIK (State University of Medan, 2021)
The objectives of this study were to find out meanings, what, how, and why the meanings were realized in the Gotilon Batak Toba Ceremony in Dolok Sanggul Humbang Hasundutan. This study was conducted using an observation study. The data of this study were taken from Gotilon Ceremony. The sources of the data were the Gotilon Ceremony in Dolok Sanggul and the informants or Raja Parhata in Dolok Sanggul. The data were analyzed by using Roland’s theory of semiotics object. The writer found the meanings on Gotilon Batak Toba Ceremony, namely: revise, support one, support two, support three, rid, speed, addition, exploitative two, exploitative three, survive, joyfulness, invitation, stay focus, keep fight, togetherness, convince, easier, kinship, honor, offering, and thanksgiving. From those materials were found that there were verbal utterances that consist of Atur biur, Angkat nomor sada, Angkat nomor dua, Angkat nomor tolu, Buang jauh-jauh, Eme, Rugi, Ponggol nomor dua, Ponggol nomor tolu, Naeng Sahat, Tambun Namboru, Hurre Alogo, Unang mekkel, Tahan nafas, Satukan, Beres. And there were symbols namely Luhutan, Marsirippa, Sipanganon, Mangamoti, and Pesta Gotilon. The signs used in Gotilon ceremony because they want to convey the meanings of the ceremony.